RAP80 regulates epithelial–mesenchymal transition related with metastasis and malignancy of cancer. Issue 3 (10th February 2016) - Park, Song Yi; Korm, Sovannarith; Chung, Hee Jin; Choi, Su jin; Jang, Jin‐Ju; Cho, Sunhee; Lim, Yong Taik; Kim, Hongtae; Lee, Joo‐Yong
Abstract : Epithelial–mesenchymal transition (EMT) has been closely related with invasive and metastatic properties of cancer. Recently, the convergence of DNA damage response and EMT in cancer development has received a great amount of scientific attention. Here, we showed that EMT is induced by the downregulation of RAP80, a well‐known regulator for DNA damage response. The knockdown of RAP80 leads to EMT‐like morphological changes and the increase of tumor sphere formation in non‐adhesive culture. Mechanistically, RAP80 controls a reciprocal regulatory axis of ZEB1 (for EMT activation) and miR200c (for EMT inhibition). The downregulation of RAP80 increases ZEB1 protein and decreases miR200c expression to activate EMT signaling in the form of drastic inhibitions of E‐cadherin, p16 and p21 expression. Using in vivo metastasis analysis, RAP80 knockdown cells are shown to dramatically metastasize into the lung and generate more malignant phenotype compared to controls. Interestingly, the expression level of RAP80 was positively correlated with the survival rate in lung adenocarcinoma and breast cancer patients. These findings indicate that RAP80 is a critical gatekeeper in impeding EMT‐induced metastasis and malignant phenotypes of cancer as well as preserving DNA integrity. Abstract : The downregulation of RAP80 activating EMT through reciprocal regulators, ZEB1 and miR200c, promoting pulmonary metastasis of cancer cells. Of consistent note, the level of RAP80 was found to negatively correlate with survival rate in lung adenocarcinoma and breast cancer patients. These findings indicate that RAP80 is a critical gatekeeper to impede metastasis of cancer as well as to secure DNA integrity.